The Gambia : Requests for Disbursement Under the Rapid Credit Facility and Modification of Performance Criteria Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper highlights The Gambia's Requests for Disbursement Under the Rapid Credit Facility and Modification of Performance Criteria Under the Extended Credit Facility Arrangement. The Gambia has also benefited from the IMF Executive Board decision of April 13, 2020 to provide debt service relief to all countries eligible for support from the International Development Association in the form of grant assistance under the Catastrophe Containment window of the Catastrophe Containment and Relief Trust. The authorities' support for social programs is being severely tested. In this context, a better targeting and timely delivery of social assistance to the most affected households and sectors is needed during the pandemic. The Central Bank of The Gambia should continue to monitor developments in the financial sector, to ensure adequate liquidity and oversight, while avoiding a blanket weakening of supervisory standards. A strengthening of market surveillance under the existing regulations will help detect and address appropriately any weakening of banks' foreign exchange positions. Maintaining a flexible exchange rate will help absorb balance-of-payments shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet